Financial Stability Frameworks and the Role of Central Banks : Lessons From the Crisis - Nier, Erlend (Washington, D.C. : International Monetary Fund, 2009)
This paper sets out general principles for the design of financial stability frameworks, starting from an analysis of the objectives and tools of financial regulation. The paper then offers a comprehensive analysis of the costs and benefits of the two main models that have emerged for modern financial systems: the integrated model, with a single supervisor outside of the central bank, and the twin-peaks model, with a systemic risk regulator (central bank) on the one hand and a conduct of business regulator on the other. The paper concludes that the twin-peaks model may become more attractive when regulatory structures are geared more explicitly towards the mitigation of systemic risk-including through the introduction of new macroprudential tools that could be used alongside monetary policy to contain macro-systemic risks; through enhanced regulation and special resolution regimes for systemically important institutions; and a more holistic approach to the oversight of clearing and settlement systems. Since the optimal solution may well be path-dependent and specific to the development of financial markets in any given country, a number of hybrid models are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet